2013
DOI: 10.1002/cne.23385
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns of Pax3, Pax6, and Pax7 Expression in the Developing Brain of a Urodele Amphibian, Pleurodeles waltl

Abstract: The onset and developmental dynamics of Pax3, Pax6, and Pax7 expressions were analyzed by immunohistochemical techniques in the central nervous system (CNS) of embryos, larvae, and recently metamorphosed juveniles of the urodele amphibian Pleurodeles waltl. During the embryonic period, the Pax proteins start being detectable in neuroepithelial domains. Subsequently, they become restricted to subsets of cells in distinct brain regions, maintaining different degrees of expression in late larvae and juvenile brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 239 publications
(455 reference statements)
3
27
1
Order By: Relevance
“…These are brain structures that form an integral part of the neuroendocrine system involving the secretion of hormones and glycoproteins into the peripheral vascular system using feedback from both the brain environment and external stimuli. Our results have shown that Ulk4 is expressed in the paraphysis of Xenopus, a neural gland derived from the roof plate of the diencephalic prosomere 3, located adjacent to the choroid plexus of the IIIv (Warren, 1905;Kappers, 1950;Jo´ven et al, 2013). Moreover, we have detected Ulk4 expression in the neurohypophysis, formed by the neural lobe and median eminence, both closely related to the hypothalamus playing a crucial role in the control of homeostasis through the release of several neurohormones (ten Donkelaar, 1998).…”
Section: Xulk4 Expression Patterns In the Forebrainmentioning
confidence: 75%
“…These are brain structures that form an integral part of the neuroendocrine system involving the secretion of hormones and glycoproteins into the peripheral vascular system using feedback from both the brain environment and external stimuli. Our results have shown that Ulk4 is expressed in the paraphysis of Xenopus, a neural gland derived from the roof plate of the diencephalic prosomere 3, located adjacent to the choroid plexus of the IIIv (Warren, 1905;Kappers, 1950;Jo´ven et al, 2013). Moreover, we have detected Ulk4 expression in the neurohypophysis, formed by the neural lobe and median eminence, both closely related to the hypothalamus playing a crucial role in the control of homeostasis through the release of several neurohormones (ten Donkelaar, 1998).…”
Section: Xulk4 Expression Patterns In the Forebrainmentioning
confidence: 75%
“…Pax3 and its homolog Pax7 belong to the same Pax subfamily. During embryogenesis, both genes are coexpressed in various tissues and are thought to subserve similar functions (Jostes et al, ; Goulding et al, ; Galli et al, ; Murdoch et al, ; Joven et al, ; Yin et al, ; Zalc et al, ). However, it has been reported that, during neural crest patterning, Pax3 and Pax7 mediate different developmental mechanisms (Maczkowiak et al, ).…”
mentioning
confidence: 99%
“…qPCR analyses showed that neural lineage genes PAX6 and SOX1 were upregulated significantly during differentiation, while mesendodermal genes T ( Brachyury ), CXCR4 , GATA6 , SOX17 , MESP1 , and EOMES were not present, suggesting the effectiveness of both neural differentiation protocols (Figures S1E and S1F). Without exogenous morphogen treatment, neural progenitors specified from both EB and AD paradigms expressed anterior genes, such as FOXG1 , EMX2 , and OTX2 , but were completely lacking in PAX7 , EN1 , or  HOXB4 , hallmark genes specific for diencephalon, midbrain, and hindbrain identities, respectively (Joven et al., 2013, Simeone, 2002) (Figures S1G and S1H). Therefore, hPSCs adopt an anterior telencephalic neural fate by default under both EB and AD conditions.…”
Section: Resultsmentioning
confidence: 99%